Molecular Methods for Haemophilus influenzae. - Herbert, M; Crook, D; Moxon, E (1998)
The speciesHaemophilus influenzae belongs to the genus Haemophilus and the family Pasteurellaceae. H influenzae are small, nonmotile, nonspore forming, Gram-negative, pleomorphic rods that range in shape from coccobacilli to long filaments. They require X and V factors (hemin and NAD, respectively) for aerobic growth, and may be facultatively anaerobic (1) Encapsulated H. influenzae are classified into six antigenically distinct serotypes (a-f), and have a clonal population structure with two major global subdivisions (I and II) (2,3). Nonencapsulated H. infuenzae (NCHi) appear to have a nonclonal population composition, but a broader analysis of NCHi in the future may reveal that the population is not so distinct from encapsulated H influenzae (4). Both encapsulated H influenzae and NCHi exhibit wide genetic diversity (5).